Clinical challenges and management of primary renal epithelioid angiomyolipoma of duplex kidney with paraneoplastic syndrome. Issue 7 (July 2021) - Wang, Pengfei; He, Jun; Wan, Xiaojun; Ren, Peng; Tang, Kaifa
Giant renal epithelioid angiomyolipoma of a duplex kidney has rarely been reported, especially in patients with paraneoplastic syndrome. The present report describes a 33-year-old man of Miao nationality who presented with a 6-month history of intermittent dull pain in the left upper abdomen that occurred after eating. Ultrasonography, intravenous pyelography, and computed tomography revealed a mass lesion localized in the left kidney and connected to the left renal artery. Radical nephrectomy was successfully performed, and the postoperative histopathological examination verified the lesion as epithelioid angiomyolipoma. Inpatient treatment for paraneoplastic syndrome was also performed. The present case is discussed in the context of the patient's clinical presentation and imaging findings, drawing attention to the challenges and management of this condition to assist clinicians in practice.